Electrophysiology of glioma: a Rho GTPase-activating protein reduces tumor growth and spares neuron structure and function. Issue 12 (13th June 2016) - Vannini, Eleonora; Olimpico, Francesco; Middei, Silvia; Ammassari-Teule, Martine; de Graaf, Erik L.; McDonnell, Liam; Schmidt, Gudula; Fabbri, Alessia; Fiorentini, Carla; Baroncelli, Laura; Costa, Mario; Caleo, Matteo
Abstract: Background: Glioblastomas are the most aggressive type of brain tumor. A successful treatment should aim at halting tumor growth and protecting neuronal cells to prevent functional deficits and cognitive deterioration. Here, we exploited a Rho GTPase-activating bacterial protein toxin, cytotoxic necrotizing factor 1 (CNF1), to interfere with glioma cell growth in vitro and vivo. We also investigated whether this toxin spares neuron structure and function in peritumoral areas. Methods: We performed a microarray transcriptomic and in-depth proteomic analysis to characterize the molecular changes triggered by CNF1 in glioma cells. We also examined tumor cell senescence and growth in vehicle- and CNF1-treated glioma-bearing mice. Electrophysiological and morphological techniques were used to investigate neuronal alterations in peritumoral cortical areas. Results: Administration of CNF1 triggered molecular and morphological hallmarks of senescence in mouse and human glioma cells in vitro. CNF1 treatment in vivo induced glioma cell senescence and potently reduced tumor volumes. In peritumoral areas of glioma-bearing mice, neurons showed a shrunken dendritic arbor and severe functional alterations such as increased spontaneous activity and reduced visual responsiveness. CNF1 treatment enhanced dendritic length and improved several physiological properties of pyramidal neurons, demonstrating functional preservation of the cortical network. Conclusions: Our findings demonstrate that CNF1 reduces glioma volume while at the same time maintaining the physiological and structural properties of peritumoral neurons. These data indicate a promising strategy for the development of more effective antiglioma therapies.